{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

Chapter 2 - 4 Now differentiate to get The only problem is...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
The chain rule is used for differentiating a function of a function We know how to differentiate x 4 , so we use the substitution u = (3x − 2) to turn the function into something that we can differentiate. This gives: y = (3x − 2) 4 Let u = 3x − 2 to give us, y = u
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 4 , Now differentiate to get: The only problem is that we want dy/dx, not dy/du, and this is where we use the chain rule. The chain rule says that So all we need to do is to multiply dy/du by du/dx. As u = 3x − 2, du/dx = 3, so 3 = 12(3x − 2) 3...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online